Cherokee Renascence in the New Republic - McLoughlin, William G. (William Gerald), 1922-1992 (Book collections on Project MUSE., 1986)
The Cherokees, the most important tribe in the formative years of the American Republic, became the test case for the Founding Fathers' determination to Christianize and "civilize" all Indians and to incorporate them into the republic as full citizens. From the standpoint of the Cherokees, rather than from that of the white policymakers, William McLoughlin tells the dramatic success story of the "renascence" of the tribe. He goes on to give a full account of how the Cherokees eventually fell before the expansionism of white America and the zeal of Andrew Jackson.